Growth of atmospheric freshly nucleated particles: a semi-empirical molecular dynamics study - Y. Knattrup; I. Neefjes; J. Kubečka; J. Elm (Aerosol Research)
When simulating new particle formation rates, collisions in the system are approximated as hard spheres without long-range interactions. This simplification may lead to an underestimation of the actual formation rate. In this study, we employ semi-empirical molecular dynamics (SEMD) at the GFN1-xTB level of theory to probe the sticking process of the monomers sulfuric acid (SA), methanesulfonic acid (MSA), nitric acid (NA), formic acid (FA), ammonia (AM), methylamine (MA), dimethylamine (DMA), and trimethylamine (TMA) onto freshly nucleated particles (FNPs). The FNPs considered are (SA)10(AM)10, (SA)10(MA)10, (SA)10(DMA)10, and (SA)10(TMA)10.